2021
DOI: 10.1016/j.cgh.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in Fecal Samples From Patients With Asymptomatic and Mild COVID-19 in Korea

Abstract: BACKGROUND & AIMS: Q6Although coronavirus disease 2019 (COVID-19) is characterized by fever and respiratory symptoms, some patients have no or mild symptoms. Severe acute respiratory syndromecoronavirus (SARS-CoV-2) has been detected in feces of patients. We investigated gastrointestinal symptoms and shedding of virus into feces of patients with asymptomatic or mild COVID-19. METHODS:We collected data from 46 patients (median age, 26 y; 46% men) with asymptomatic or mild COVID-19 (without fever and pneumonia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
140
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 20 publications
1
140
0
15
Order By: Relevance
“…Indeed, the fact that the virus had been circulating in Europe in late December 2019 has already been demonstrated by a French study ( Deslandes et al, 2020 ) that retrospectively analysed samples taken from intensive care patients with influenza-like symptoms in Paris, and found one SARS-CoV-2 positive respiratory sample in a French resident who had not visited China and who had been hospitalised on December 27, 2020. Considering the incubation period of COVID-19 - 6.4 days on average ( Wang et al, 2020 ) - as well as evidence showing that viral shedding may occur in asymptomatic patients ( Jiang et al, 2020 ; Park et al, 2020 ; Tang et al, 2020 ), it is conceivable that the virus was circulating and being released into the sewage in the Paris area roughly at the same time as in northern Italy, as indicated by our positive sewage samples.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Indeed, the fact that the virus had been circulating in Europe in late December 2019 has already been demonstrated by a French study ( Deslandes et al, 2020 ) that retrospectively analysed samples taken from intensive care patients with influenza-like symptoms in Paris, and found one SARS-CoV-2 positive respiratory sample in a French resident who had not visited China and who had been hospitalised on December 27, 2020. Considering the incubation period of COVID-19 - 6.4 days on average ( Wang et al, 2020 ) - as well as evidence showing that viral shedding may occur in asymptomatic patients ( Jiang et al, 2020 ; Park et al, 2020 ; Tang et al, 2020 ), it is conceivable that the virus was circulating and being released into the sewage in the Paris area roughly at the same time as in northern Italy, as indicated by our positive sewage samples.…”
Section: Discussionmentioning
confidence: 64%
“…The viral load in the faeces of COVID-19 patients was estimated between 10 3 and 10 7 copies/mL, depending on the infection course (reviewed in Foladori et al, 2020 ). These patients have been shown to shed the virus in their stools even if asymptomatic or pre-symptomatic ( Jiang et al, 2020 ; Park et al, 2020 ; Tang et al, 2020 ). Sewage samples can thus be used to monitor the levels of virus circulating in the population, an approach called wastewater-based epidemiology (WBE).…”
Section: Introductionmentioning
confidence: 99%
“…The individual testing of SARS-CoV-2 by qPCR or alternative analytical methods is not enough to capture how coronavirus is spread among the human communities and how SARS-CoV-2 infects asymptomatic individuals can be detected as super-spreaders for COVID-19 34 . Recently, patients from Korea with COVID-19 in quarantine showed that the shedding of virus into feces persisted until day 50 after diagnosis even in patients with asymptomatic or mild disease, or with no gastrointestinal symptoms 35 . This information is pivotal to establish risk factors for COVID-19, preventing the severity and socio-economic impacts of COVID-19 outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…31 Based on the CT values, viral load appears to be highest in the nasal/nasopharyngeal-derived specimens, and is detectable at multiple sites simultaneously. 31 Viable virus has also been documented in fecal material from infected patients, 31,41 raising the theoretical possibility that fecal or fecal/oral transmission may be a potential route of spread as well 41,42 -although this has not been conclusively documented to-date. Viral RNA has also been detected in seminal fluid in some series, 43 but not in others, 44 and does not appear detectable in urine 31,44 or vaginal fluid.…”
Section: Testing and Transmissionmentioning
confidence: 99%